Edukasi Gizi dan Suplemen Vitamin D untuk Perbaikan Asupan Zat Gizi, Komposisi Tubuh, dan Status Vitamin D Atlet Sepak Bola: Nutrition Education and Vitamin D Supplementation Improving Nutrition Intake, Body Composition, and Vitamin D Status of Soccer Athlete - Kurdanti, Weni; Wijanarka, Agus; Penggalih, Mirza Hapsari Sakti Titis (Universitas Airlangga, 2024)
Background: The success of soccer athletes is influenced by physical, mental, and genetic factors, with nutritional status significantly affects youth soccer performance in Indonesia by 69.8%. Body composition and somatotype are critical components of nutritional status. Biochemical indicators such as creatine kinase (CK) and vitamin D levels provide insights into the impact of training and diet on athletes. Objectives: To determine the effect of nutritional interventions on improving the intake and body composition of athletes characterized by the value of creatinine kinase levels and vitamin D levels of athletes and an increase in VO2 Max values as performance indicators. Methods: This experimental study used a pre-post control trial design involving 39 subjects who were divided into treatment (20 athletes) and control (19 athletes) groups for one month. The treatment group received nutrition education (classroom, individual, and nutrition assistance) and vitamin D supplementation of 800 IU per day, while the control group was only monitored. The exercise was adjusted to the coach's program. Results: Energy, protein, and carbohydrate intakes were deficient among athletes, although fat intake was adequate. CK levels were within normal limits. All athletes in the control group exhibited vitamin D deficiency, compared to 90% in the intervention group, despite supplementation showing modest improvement. Conclusions: Vitamin D supplementation has a significant effect on increasing blood vitamin D levels. This study reinforces the importance of education and supplementation-based nutrition interventions to improve the nutritional status and performance of soccer athletes.